Strategi Pembelajaran dan Kemampuan Guru Kelas - Fahrurrozi, Muhammad; Mohzana, Mohzana; Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the ability of elementary school class teachers in Central Lombok in preparing learning strategy plans. This research is qualitative. The data in this study are in the form of thematic lesson plans for the Central Lombok State Elementary School class theme 1 â€œLife Savingsâ€ sub-theme 1 learning 3, sub-theme 2 learning 2, sub-theme 3 learning 6, sub-theme 4 learning 1. Data analysis using data analysis techniques qualitative data analysis can be done simultaneously with the process of data collection, data interpretation, and narrative writing. The results showed that the formulation of indicators 3.1.1 in sub-theme 1 learning 3 was not appropriate, the subject of the formulation of learning objectives and teaching materials in sub-theme 3 learning 6 was not appropriate, items that did not refer to indicators in sub-theme 1 learning 3, and the use of operational words which is less precise in the formulation of learning objectives in sub-theme 3 learning 6. In conclusion, the class teacher of the Central Lombok State Elementary School is related to being able to formulate learning strategy plans. Keywords: Ability, Class Teacher, Learning Strategy Plan.